Prime-boost vaccination with attenuated Salmonella Typhimurium ΔznuABC and inactivated Salmonella Choleraesuis is protective against Salmonella Choleraesuis challenge infection in piglets - Alborali, Giovanni Loris (BMC Vet Res, 2017)
BACKGROUND: Salmonella enterica serovar Choleraesuis (S. Choleraesuis) infection causes a systemic disease in pigs. Vaccination could represent a solution to reduce prevalence in farms. In this study, we aimed to assess the efficacy of an attenuated strain of Salmonella enterica serovar Typhimurium (S. Typhimurium ΔznuABC) against S. Choleraesuis infection. The vaccination protocol combined priming with attenuated S. Typhimurium ΔznuABC vaccine and boost with an inactivated S. Choleraesuis vaccine and we compared the protection conferred to that induced by an inactivated S. Choleraesuis vaccine. METHODS: The first group of piglets was orally vaccinated with S. Typhimurium ΔznuABC and boosted with inactivated S. Choleraesuis, the second one was intramuscularly vaccinated with S. Choleraesuis inactivated vaccine and the third group of piglets was unvaccinated. All groups of animals were challenged with a virulent S. Choleraesuis strain at day 35 post vaccination. RESULTS: The results showed that the vaccination protocol, priming with S. Typhimurium ΔznuABC and boosted with inactivated S. Choleraesuis, applied to group A was able to limit weight loss, fever and organs colonization, arising from infection with virulent S. Choleraesuis, more effectively, than the prime-boost vaccination with homologous S. Choleraesuis inactivated vaccine (group B). CONCLUSION: In conclusion, these research findings extend the validity of attenuated S. Typhimurium ΔznuABC strain as a useful mucosal vaccine against S. Typhimurium and S. Choleraesuis pig infection. The development of combined vaccination protocols can have a diffuse administration in field conditions because animals are generally infected with different concomitant serovars.